The Effect of Parkinson’s Disease on Patients Undergoing Lumbar Spine Surgery - Jeremy Steinberger; Jeffrey Gilligan; Branko Skovrlj; Christopher A. Sarkiss; Javier Z. Guzman; Samuel K. Cho; John M. Caridi (Parkinson's Disease)
Study Design. Retrospective Database Analysis. Objective. The purpose of this study was to assess characteristics and outcomes of patients with Parkinson’s disease (PD) undergoing lumbar spine surgery for degenerative conditions. Methods. The Nationwide Inpatient Sample was examined from 2002 to 2011. Patients were included for study based on ICD-9-CM procedural codes for lumbar spine surgery and substratified to degenerative diagnoses. Incidence and baseline patient characteristics were determined. Multivariable analysis was performed to determine independent risk factors increasing incidence of lumbar fusion revision in PD patients. Results. PD patients account for 0.9% of all degenerative lumbar procedures. At baseline, PD patients are older (70.7 versus 58.9, p<0.0001) and more likely to be male (58.6% male, p<160.0001). Mean length of stay (LOS) was increased in PD patients undergoing lumbar fusion (5.1 days versus 4.0 days, p<0.0001) and lumbar fusion revision (6.2 days versus 4.8 days, p<180.0001). Costs were 7.9% (p<0.0001) higher for lumbar fusion and 25.2% (p<0.0001) higher for lumbar fusion revision in PD patients. Multivariable analysis indicates that osteoporosis, fluid/electrolyte disorders, blood loss anemia, and insurance status are significant independent predictors of lumbar fusion revision in patients with PD. Conclusion. PD patients undergoing lumbar surgery for degenerative conditions have increased LOS and costs when compared to patients without PD.